Pengaruh Model Project Based Learning Terhadap Hasil Belajar Penyajian Data di Kelas IV Sekolah Dasar - Mayang Sari; Melva Zainil (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This study aims to determine the effect of the Project Based Learning model on the learning outcomes of data presentation in Elementary School Cluster II District Guguak District 50 City. The type of this research is quantitative research with the experimental method and the design of Quasi Exsperiment, with the form of Nonequivalent pretest-posttest control group design. The sample technique used was cluster random sampling with a sample consisting of two classes. The results showed that the average value of the Experimental Post-test class using the Project Based Learning model was 77, 6 and the control class using conventional learning was 65.6. This shows that learning outcomes with the Project Based Learning model are influential compared to conventional learning. Analysis of the data of the two groups using the t test, obtained results of tcount 4.61 and ttable at a significant level of 0.05 of 2.010 so that tcount> t table. So Ho is rejected and Ha is accepted.